MOTIVASI BELAJAR SISWA: KONSEP, FAKTOR DAN UPAYA PENINGKATANNYA - Ratna Swari, Dewi; Abdurrohim; Siti Khulasoh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning motivation is one of the key components that influences students' success in the learning process. Students with high learning motivation tend to be more active, diligent, and enthusiastic in achieving their academic goals. This article aims to explore the concept of student learning motivation, the factors that influence it, and the efforts that can be made to enhance it. This study uses a literature review method by examining various relevant sources, such as books and scholarly journals. The research results show that learning motivation is influenced by both intrinsic and extrinsic factors, including learning interest, learning environment, and the role of teachers in the learning process. Therefore, to achieve optimal learning outcomes, various efforts are needed to enhance students' learning motivation.